2016
DOI: 10.5028/jatm.v8i3.568
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management Patterns Model for a Flight Test Environment

Abstract: This paper investigates how Knowledge Management patterns in a Brazilian Air Force flight test environment can be simulated using a System Dynamics approach. The research has been conducted initially by a literature review on the main Knowledge Management and System Dynamics theories. Data for this research has been collected in a previous study consisted of documental research regarding the flight test environment Knowledge Management and a questionnaire-based survey which identified both a low Knowledge Mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The authors reported the level of knowledge sharing liquidation, the level of knowledge requiring barrier, and the level of knowledge gap as outputs from the simulation. Follador & Trabasso [40] assessed the Air Force's suitability for KM. The authors have produced a CLD describing the KMP.…”
Section: Businessmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported the level of knowledge sharing liquidation, the level of knowledge requiring barrier, and the level of knowledge gap as outputs from the simulation. Follador & Trabasso [40] assessed the Air Force's suitability for KM. The authors have produced a CLD describing the KMP.…”
Section: Businessmentioning
confidence: 99%
“…According to Table 3, the SD was utilised as a tool for knowledge management in the following domains (in ascending order): business, miscellaneous management disciplines, software development, general, food system, health, miscellaneous knowledge areas, other, and product-related area (RQ4). The following articles are examples for each category in Figure 7: business [35,37,38,43,50]; miscellanies management disciplines [49,52,53]; miscellanies knowledge area [41,48,54]; education [42,56,57] knowledge management system [46,47]; general [40,44,58]; product-related area [45,70]; software development [62,77].…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation